Avulsion fracture of the straight and reflected heads of rectus femoris. Issue 3 (September 1992) - Deehan, D J; Beattie, T F; Knight, D; Jongschaap, H
Abstract : We present a rare case of avulsion fracture of the reflected head of rectus femoris. This occurred in a 13-year-old male footballer. Diagnosis was made with pelvic radiology and treatment was bed rest and analgesia.